2018
DOI: 10.1177/1403494818799597
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of complementary and alternative medicine use among Arab immigrants in Denmark: A qualitative study

Abstract: Aims: The aim of this study was to explore patterns of complementary and alternative medicine use among Arab immigrants in Denmark, in order to increase insight into the hidden practices of this ethnic group. Methods: In this study, 21 Arab immigrants in Denmark were interviewed in Arabic. A purposive strategic sample was recruited from mosques, a healthcare center and by snowballing. Semi-structured interviews were conducted, then audiotaped and transcribed. The analysis was conducted according to Malterud’s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Although some of the acquired results are consistent with these findings, this research highlights that unlike other European countries, acupuncture and chiropraxis are less frequently reported in Slovakia. Eastern Europe is more ethnically homogenous than many other Western regions, and several studies have shown that some CAM treatments are embedded in health patterns of various ethnic minorities (Zeid et al, 2019). These are defined as group of people who have different set of traditions, language, culture, or religion from that of the majority of individuals living in particular society.…”
Section: Interpretation Of Key Resultsmentioning
confidence: 99%
“…Although some of the acquired results are consistent with these findings, this research highlights that unlike other European countries, acupuncture and chiropraxis are less frequently reported in Slovakia. Eastern Europe is more ethnically homogenous than many other Western regions, and several studies have shown that some CAM treatments are embedded in health patterns of various ethnic minorities (Zeid et al, 2019). These are defined as group of people who have different set of traditions, language, culture, or religion from that of the majority of individuals living in particular society.…”
Section: Interpretation Of Key Resultsmentioning
confidence: 99%
“…Another reason for the wide acceptance of CAM in Western Europe is the more multicultural character of these societies, in contrast to the more homogenous Eastern region. Several studies have proven that special forms of CAM are embedded in the health behaviour of various ethnic minorities [28, 29].…”
Section: Discussionmentioning
confidence: 99%
“…Most studies on the health of immigrants showed that immigrants bring with them their cultural health beliefs and practices, that often influence their decisions to access their preferred health approach (Bartlett et al, 2012;Kong & Hsieh, 2012;Zeid et al, 2019). Health beliefs and practices of immigrants are embedded in their inherited culture.…”
Section: Barriers To Access Western Health Care Servicesmentioning
confidence: 99%